1980
DOI: 10.1038/clpt.1980.238
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine kinetics after single and repeated oral doses

Abstract: In reports on hydralazine kinetics plasma hydralazine levels have been measured with nonspecific assay techniques. The techniques used also include acid-labile hydralazine metabolites and therefore markedly overestimate hydralazine levels. We have developed specific, sensitive assay methods for the measurement of hydralazine and its major plasma metabolite, hydralazine pyruvic acid hydrazone (HPH). By these methods, we determined hydralazine and HPH kinetics after single and repeated oral doses of hydralazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 3 publications
4
20
1
Order By: Relevance
“…Furthermore, as incomplete inhibition of LDL modification appears to be sufficient to prevent scavenger receptor recognition and particle uptake, it is possible that even low levels of these carbonyl-scavenging compounds may be beneficial. After oral dosing in humans hydralazine and metformin can reach micromolar concentrations and aminoguanidine concentrations of tens of micromoles [32,[45][46][47], levels that are considerably in excess of those of the reactive aldehydes (see above). It is therefore conceivable that these compounds may act as efficient scavengers of reactive aldehydes in vivo, especially as it has been demonstrated that equimolar levels of these drugs are sufficient to induce significant protection against aldehyde-mediated LDL modification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as incomplete inhibition of LDL modification appears to be sufficient to prevent scavenger receptor recognition and particle uptake, it is possible that even low levels of these carbonyl-scavenging compounds may be beneficial. After oral dosing in humans hydralazine and metformin can reach micromolar concentrations and aminoguanidine concentrations of tens of micromoles [32,[45][46][47], levels that are considerably in excess of those of the reactive aldehydes (see above). It is therefore conceivable that these compounds may act as efficient scavengers of reactive aldehydes in vivo, especially as it has been demonstrated that equimolar levels of these drugs are sufficient to induce significant protection against aldehyde-mediated LDL modification.…”
Section: Discussionmentioning
confidence: 99%
“…111 This difference appeared to be due to a change in the bioavailability of the drug which decreased from 33% in slow acetylators to less than 10% in rapid acetylators. 112 A more common consequence of the polymorphic acetylation of therapeutic agents is an increase in the frequency and severity of side-effects associated with either the rapid or slow phenotype (Table 3). These adverse effects often arise as the result of a shift in the metabolic pathways responsible for the activation and detoxification of the drug.…”
Section: Nat and Drug Responsementioning
confidence: 99%
“…In fast acetylators, the oral availability of hydralazine is 7 to 16%, reflecting presystemic metabolism by NAT2. Slow acetylators have higher oral availability (30 -40%), and hydralazine pyruvic acid hydrazone is the main plasma metabolite, resulting from reaction with pyruvic acid in plasma (Reece et al, 1980;Shepherd et al, 1980). The AUC of hydralazine is Ïł3-fold higher in slow acetylators, and this may increase to 6-to 7-fold higher with multiple dosing (Reece et al, 1980;Shepherd et al, 1980).…”
Section: A Acetyltransferasementioning
confidence: 99%